Global Health Governance and Its Role in Health Equity: The Case of Covid-19 - Abu El Kheir-Mataria, Wafa (AUC Knowledge Fountain, 2023)
In the globalized world, we are living in, health became the joint responsibility of individuals, their governments, and the global health governance system. Moreover, based on the right to health, health equity is increasingly in demand, and adopting it to a global level has become an even more complex task to realize. This thesis is focuses on health equity at a global level. The main research questions addressed are: Is health equity present at an intercountry /global level? how is it related to Global Health Governance (GHG)? Is GHG performing well in achieving health equity? what are the reasons behind this performance? What needs to be changed for better future performance? And finally, the importance of different GHG actors in the current GHG system and how their roles might change following their performance during Covid-19? To answer these questions, different methodologies were used. First, a systematic scoping review was conducted to define the current state of practice based on the published literature in the relevant areas and to formulate the base for this thesis. Second, a meta-analysis was performed to address one of the behavioral determinants of health leading to health equity, it addressed parental acceptance to vaccinate their children against Covid-19 in Low and Middle-Income Countries (L&MICs). The result of this meta-analysis was compared to High-Income Countries (HICs) to delineate differences in behavior according to countries’ economies. Third, a concentration index and its decomposition analysis were conducted to define; first, the presence of health inequities at the inter-country level according to countries’ economic status, and second to determine the factors contributing to these health inequities, when present. Forth, a Delphi analysis was completed to reach a panel expert consensus on GHG performance during Covid-19, as well as the factors behind this performance and what future changes are needed for better health equity. Finally, a social network analysis was done to determine the centrality of GHG actors during Covid-19 and whether actors’ centralities would change following the Covid-19 crisis. The scoping systematic review demonstrated that research in the field concerning GHG, health equity and Covid-19 concentrated on human rights and equity in the context of Covid-19 as well as on the needed GHG structural changes, laws and regulations, the political and economic power role in decision making, and the private sector role. The meta-analysis provided evidence that the proportion of parents in L&MICs accepting to vaccinate their children against Covid-19 (49%) is lower than the global level due to parents’ concerns about vaccine efficacy, safety, and possible side effects. The concentration index analysis clearly showed that the distribution of the Covid-19 vaccine among countries is inequitable, where rich countries had a higher ability to secure the vaccine than poor countries. The decomposition of the concentration index strongly suggested that the main factors contributing to in the inequity in the distribution of Covid-19 vaccines are: the political stability of the country, the level of universal health coverage, and the power imbalance in GHG. The Delphi consensus study concluded that GHG performance in Covid-19 was not optimal, which in turn limited the achievement of Covid-19 vaccines’ global equity. For better GHG performance, GHG structure, actors’ representation, accountability system, and underlying priorities and values require future modification. Lastly, the social network analysis highlighted the following: first, few actors are central to GHG, namely: WHO, UNICEF, governments, funding actors and research agencies. Second, legitimacy, financial resources and broad connections with other important actors are factors that enhance the centrality of actors. And third, certain actors’ centralities are forecasted to likely change following Covid-19. This thesis investigated and delineated the connection between GHG and health equity and explored the factors affecting this connection. In doing so many questions arose regarding GHG, equity and the underlying factors. The final recommendation based on this research is that further investigation, based on expanded quality data is imperative. The following areas, in particular, are suggested: what determines the structure and functionality of GHG – the actors or the events? How to achieve better/more equitable actors’ representation in GHG? How to concentrate on human rights as the main value for GHG decisions? What political and legal reform and accountability measures are needed and how would they be enforced? The power dynamics in decision-making in GHG and its consequences.